Accelerated therapeutic development during COVID-19: insights, regulatory strategies, and recommendations for future pandemic preparedness - Katayama, Miyuki; Shikano, Mayumi (Frontiers in Medicine, 2025)
BackgroundThe clinical development of therapeutics for COVID-19 proceeded at an extraordinary pace. Given the lack of studies evaluating this experience systematically, we analyzed the clinical development methods for COVID-19 therapeutics to determine strategies for shortening the clinical development period in preparation for future pandemics.MethodsWe confirmed the US-FDA review documents for fourteen products that underwent Emergency Use Authorization (EUA) in the US during the COVID-19 pandemic to examine the time required for clinical development and regulatory review and the submitted data for EUA.ResultsSix of the fourteen products with clinical study data for other indications were evaluated in fewer studies than new molecular entities. The application data for each product included the stipulated content, and placebo-controlled comparative studies were included for all products. Clinical development measures were adopted, including adaptive protocol design, nonsequential phase development, and clinical dose adaptation based on non-clinical study results.ConclusionProducts with clinical study data for other indications are advantageous for early approval. However, early approval of new molecular entities is also important because they may not be sufficiently effective against new infectious diseases. It would be effective to approve a product promptly for a limited target population at first and then gradually expand it as data becomes more abundant. To prepare for future pandemics, we recommend establishing a framework for identifying candidates from existing products, managing and disseminating information in emergencies at various levels, and clarifying the conditions for applying regulatory flexibility to encourage pharmaceutical companies to make early decisions regarding clinical development.